Prática de reescrita do gênero fábula com enfoque no uso dos sinais de pontuação - Nascimento, Juliana Fontes dos Santos (2020)
The reflection about the problematic of reading and writing is of paramount importance at school. Analyzing the studies and activities that enable the formation of proficient readers and writers is something necessary so that paths for renewal and qualification in pedagogical practice can be presented. Thus, this research aims to propose a work of reading and rewriting the genre fable with a focus on the use of punctuation marks. The need for studies on this subject consists in the fact that there is little exploration and reflection on punctuation both in the field of reading and in writing, given the importance of this content for the constitution of meanings in the texts. Besides to this, it is also proposed to show that the didatic book still does not present a satisfactory approach regarding the teaching of punctuation, since it brings a heap of rules applied at the phrasal level, thus making teaching decontextualized and inefficient. Thus, in this context, we seek to present proposals for teaching and learning punctuation from an enunciative-discursive perspective. Based on the assumption that the use of punctuation is a socio-historical construction, as it involves a set of social practices, we seek the contributions of Ferreiro (1996), Rocha (1997), Cardoso (2002), Dahlet (2006) and Ferrarezi (2018), in order to present the historical path that the use of punctuation has taken up to the present day, as well as to present the concepts of punctuation and the approach of these marks carried out at school. In the discursive domain about working with the textual genre and under the perspective of Sociodiscursive Interactionism, the contributions of Bronckart (2012), Dolz and Schnewuly (2004) and Marcuschi (2008). In order to highlight the characteristics of the fable genre, Coelho (2000) and Bagno (2002) contributed significantly. Under the light of the theoretical framework, we adopted action research as a methodological procedure, which gave us support to develop activities in the format of a didactic sequence, in a 9th grade class, from Elementary School II, located in the city of Lagarto-SE. Aiming to offer subsidies for a new teaching-learning practice of punctuation in an enunciative-discursive perspective, this research presents in its composition a pedagogical notebook consisting of activities associated with the fable genre that contribute to the reflection and the conscious use of these signs in the text written.